Reinvención Del Contador Público Para Estar En La Era De La Inteligencia Artificial (2023)
In this monograph a study was made on the history of accounting and how it has had to reinvent itself with the changes brought by the Artificial Intelligence revolution. Firstly, it was based on the concepts of Accounting and Artificial Intelligence from the point of view of several authors such as Enrique Ruiz Arias, in addition to identifying through history the changes that public accounting professionals have had to face.